2008
DOI: 10.1002/lsm.20663
|View full text |Cite
|
Sign up to set email alerts
|

Viability of human septal cartilage after 1.45 µm diode laser irradiation

Abstract: Background and Objectives Chondrocyte viability following laser irradiation and reshaping has not been established for human nasal septal cartilage. Knowledge of the relationship between thermal injury and laser dosimetry is needed in order to optimize septal laser cartilage reshaping. The objective of this study was to determine the depth and width of thermal injury in human septal cartilage following laser irradiation. Study Design/Materials and Methods Excess fresh nasal septal cartilage sections from rhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…18,19,21-23 To assess the viability of chon-drocytes, specimens were stained with the fluorophores calcein acetomethoxy and ethidium homodimer 1 and were imaged with a confocal microscope (Meta 510; Carl Zeiss LSM). Digital images were recorded and analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…18,19,21-23 To assess the viability of chon-drocytes, specimens were stained with the fluorophores calcein acetomethoxy and ethidium homodimer 1 and were imaged with a confocal microscope (Meta 510; Carl Zeiss LSM). Digital images were recorded and analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Assessing chondrocyte viability using laser confocal microscopy and live-dead fluorescent assays is a well-established technique, 15,16 aiding the optimization of EMR dosimetry and geometry of electrode placement. Confocal microscopy identified some regions of tissue injury, which were spatially limited to the immediate vicinity around each needle electrode up to 1.2-mm away.…”
Section: Commentmentioning
confidence: 99%
“…24,25,2729 Confocal microscopy identified a sharply demarcated, hemispherically shaped region of nonviable cells at the laser target. After irradiation at 6 W for 2 seconds, the largest extent of nonviable cells was 0.8 mm deep with a 1.9-mm surface diameter (Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
“…A cell viability assay (LIVE/DEAD; Molecular Probes, Eugene, Oregon) in conjunction with fluorescent confocal microscopy (Model LSM 510 META; Carl Zeiss, Jena, Germany) was performed on the cross-sectional slice by following the protocol described by Choi et al 25 In the resulting images, green fluorescence indicated live cells, whereas red fluorescence indicated dead cells with compromised cell membranes. The maximum area of thermal damage was determined by measuring the depth and surface diameter of the red fluorescing region for 3 samples per dosimetry setting.…”
Section: Methodsmentioning
confidence: 99%